LEGAL CLASSIFICATION OF CIVIL LITIGATION IN THE ACTIVITIES OF A LAWYER - Shakhzoda Rustamova (Scholar Express Journals, 2024)
This article covers the objective legal framework of the concepts of the lawyer – as a contractual (voluntary) representative, the lawyer's activity in preparing to take a vote of confidence and attend court as a representative, the participation of a lawyer at the stage of initiating a case and preparing a court hearing,the participation of a lawyer in proceedings .
Keywords: the lawyer's activity; objective legal framework